Editing of homologous globin genes by nickase-deficient base editor mitigates large intergenic deletions in HSPCs - Anila George; Poornasree Sadanandan; Nithin Sam Ravi; B. Vaishnavi; Srujan Marepally; Saravanbhavan Thangavel; Shaji R. Velayudhan; Alok Srivastava; Kumarasamypet M Mohankumar (Elsevier, 2024)
Recent studies have shown that base editing, even with single-strand breaks, could result in large deletions of the interstitial regions while targeting homologous regions. Several therapeutically relevant genes such as HBG, HBB, CCR5, and CD33 have homologous sites and are prone for large deletion with base editing. Although the deletion frequency and indels observed are lesser than what is obtained with Cas9, they could still diminish therapeutic efficacy. We sought to evaluate whether these deletions could be overcome while maintaining editing efficiency by using dCas9 fusion of ABE8e in the place of nickaseCas9. Using guide RNAs (gRNAs) targeting the γ-globin promoter and the β-globin exon, we evaluated the editing outcome and frequency of large deletion using nABE8e and dABE8e in human HSPCs. We show that dABE8e can edit efficiently while abolishing the formation of large interstitial deletions. Furthermore, this approach enabled efficient multiplexed base editing on complementary strands without generating insertions and deletions. Removal of nickase activity improves the precision of base editing, thus making it a safer approach for therapeutic genome editing.